As múltiplas vozes constitutivas do personagem-escritor no romance A Festa de Ivan Angelo - Soares, Vanderleia Cassiana Helmer (2007)
The present study aims to reveal the formation of the writer-character on the novel The Party, by Ivan Ângelo. In order to develop the analysis, the various voices which permeate the story are taken as reference, considering the socio-historical and ideological relations inherent to the process of formation of the writer-character on the different positions of the subject which he occupies. About the framing of this research, at first there is an approach to the theoretical and conceptual assumptions which will guide the work. There is also the presentation of the notions which are pertinent to the study proposed to do, which are: the concept of discoursive formation; the notion of enunciation; the notion of subject; the notions of discourse and interdiscourse and the notions of heterogeneity and polyphony. Therefore, one could say that the formation of the subject (character-writer) is processed on and by the discourse, in which who speaks does it from a certain location, on a certain situation and group of circumstances. That is the reason why the subject is socio-historically and ideologically constituted. On a second moment, the concept of authorship is presented based on the studies of Foucault. The subject, when occupies a position on the empty space of the author-function, is affected by its location on the social structure, which establishes conflicts on the production of meaning and shows that signification is always a process. On the third chapter the social and historical conditions in which the novel The Party was produced are presented, for the fragments embraced by the research could be analyzed. On the fourth chapter brings the analysis of the ten fragments presented by the narrator as the notes of the writer , on the Before the party chapter , and one fragment in which the narrator shows the demise of the writer-character on the last chapter, After the party . These fragments form the sayings of the (fictional) writer, who is a character as well, and who attempts, from this position of writer, to control the meanings and to grant unity to the discourse. After the analysis, however, they prove themselves to be scattered and objectors to the socio-historical moment in which the writer-character finds himself inserted in.